The Effectiveness of Boiled Eggs on the Healing of Perineal Wounds in Postpartum Mothers - Lili Anggraini; Hatifah; Teti Kristiani Harefa; Karwiyah; Welly Octawiyati; Novia Bintang Putri (Jurnal Penelitian Pendidikan IPA, 2025)
Perineal wounds are a common complication experienced by postpartum mothers during childbirth. Delayed wound healing increases the risk of infection and discomfort during the puerperium. Nutritional intake, particularly protein, plays a vital role in supporting tissue regeneration. Boiled eggs are known as an affordable and highly nutritious source of animal protein. This study aimed to determine the effectiveness of boiled egg consumption for accelerating perineal wound healing among postpartum mothers at Klinik Multazam in 2025. A quantitative approach with a cross-sectional design was used, involving 60 postpartum mothers, of which 32 had perineal wounds. Samples were obtained through total sampling. Data were collected using observation sheets and analyzed with the chi-square test. The results showed that most respondents who regularly consumed boiled eggs (78.9%) experienced faster wound healing within (<6 days). The chi-square test yielded a p-value of 0.008 (<0.05), indicating a significant relationship between boiled egg consumption and the speed of perineal wound healing. Regular consumption of boiled eggs was shown to be effective in accelerating perineal wound healing among postpartum mothers. This simple nutritional intervention may serve as a promotive and preventive effort in postpartum midwifery care.